Analysis of the Fatwa of the Indonesian Ulema Council on the Legal Consequences of Violations of Divorce Taklik in Momunu District, Buol Regency - Haruna, Amin; Abidin, Zainal; Jumat, Gani (State Islamic University Datokarama Palu, 2023)
Taklik talak is the groom's divorce promise after signing the marriage contract. Taklik divorce is stated in the marriage certificate and is required for a specific event in the future. Seeing the habit of reading taklik talak in the Momunu sub-district, there are not a few cases of violations of taklik talak which are caused by the economy, domestic violence, extramarital affairs, and others, so there is no harmony in a household relationships. This study aimed to analyze the implementation of taklik divorce in Momunu district—research using qualitative methods. The data collection techniques are carried out through observation, interviews, and documentation. At the same time, data analysis is done by reducing, presenting, and verifying data. So that the data obtained has credibility and validity so that processing techniques and data analysis and checking the validity of the data are carried out. This study's results indicate two legal consequences from violations of taklik divorce in the sub-district of Momunu, namely the Khulu divorce lawsuit and the fulfillment of Iwadh Taklik Talak. After deeply analyzing the fatwa of the Indonesian Ulema Council, the authors conclude that the taklik divorce in marriage and its pronunciation has no urgency and is no longer relevant today. Regarding violations of taklik divorce committed by several parties, the wife may impose divorce because the husband has left or the husband's whereabouts are unclear. According to the Malik school of thought, taklik divorce is considered divorce ba'in, while according to the Ahmad school of thought, it is fasakh. This is to prevent harm to the woman. The wife may also ask for a divorce if the husband leaves her.